Implikasi Pengelolaan Pembelajaran Bermutu Pada Kelas Unggulan - Suresmi Suresmi (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
The existence of a superior class in madrasah is an institution that is specifically designed and developed systematically, adequate facilities / infrastructure, curriculum, qualified teaching and education staff, and so on. The existence of a superior class can increase the competitiveness of madrasas and the bargaining position of madrasas as superior madrasas will be even stronger. To increase the competitiveness of these madrasas as superior madrasas, it is necessary to properly manage quality learning. This article discusses planning, organizing, implementing, evaluating and the implications of quality learning in superior classes at MTsN 2 Bandar Lampung and at MTsN 2 Tanggamus. This research is a field research, using a qualitative approach with a multisite study design. Data collection techniques using in-depth interviews, observation and documentation. descriptive data analysis techniques with the Analysis Interactive Model. The results of the study, learning in superior classes at MTsN 2 Model Bandar Lampung and MTsN Model Talang Padang are designed through planning, organizing, implementing, and evaluating middle input through superior processes based on the spirit of spiritual learning that can strengthen the learning system. The implications of managing quality learning in superior classes at MTsN 2 Bandar Lampung and at MTsN 2 Tanggamus are: The establishment of an integrated learning system and the establishment of teacher standardization.